2020
DOI: 10.2139/ssrn.3602755
|View full text |Cite
|
Sign up to set email alerts
|

The Distributional Impacts of Early Employment Losses from COVID-19

Abstract: COVID-19 substantially decreased employment, but the effects vary among demographic and socioeconomic groups. We document the employment losses in April 2020 across various groups using the U.S. Current Population Survey. The unemployment rate understates employment losses. We focus on the percentage of the civilian population that is employed and at work. Young persons experienced the largest employment losses. Individuals with less education and lower family income experienced much larger employment losses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 4 publications
2
12
0
Order By: Relevance
“…With respect to the literature, these results may shed light on the evidence provided in studies such as by Bonacini, Gallo, and Scicchitano (2020) who have shown that working from home (due to social distancing) increases income inequality among employees, potentially due to the heterogeneity across education levels. This is also consistent with the idea that lower‐income people have to continue working outside during COVID‐19, as they have experienced higher unemployment rates as shown in studies such as by Cho and Winters (2020).…”
Section: Estimation Resultssupporting
confidence: 89%
“…With respect to the literature, these results may shed light on the evidence provided in studies such as by Bonacini, Gallo, and Scicchitano (2020) who have shown that working from home (due to social distancing) increases income inequality among employees, potentially due to the heterogeneity across education levels. This is also consistent with the idea that lower‐income people have to continue working outside during COVID‐19, as they have experienced higher unemployment rates as shown in studies such as by Cho and Winters (2020).…”
Section: Estimation Resultssupporting
confidence: 89%
“…A UK study found that especially those with a drop in income were more likely to experience food insecurity during the corona crisis ( Loopstra, 2020 ) which includes eating less by skipping meals or not eating for a whole day. As individuals with low educational levels are more likely to experience larger employment losses due to the corona crisis than those with high educational levels ( Cho & Winters, 2020 ), this could be a potential mechanism explaining this outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the research so far seems to unanimously show that the workers hit the hardest by the crisis are women, young, low-educated (Béland et al, 2020a;Bick and Blanding, 2020;Cho and Winters, 2020;Cowan, 2020;Montenovo et al, 2020) or with an ethnic minority or migration background (Béland et al, 2020a;Borjas and Cassidy, 2020;Cho and Winters, 2020;Cowan, 2020;Fairlie et al, 2020;Montenovo et al, 2020). Nevertheless, some evidence suggests that during the initial stages of the crisis men might have been disproportionately affected (Béland et al, 2020a) and that some older workers might have chosen to go on early retirement (Coibion et al, 2020;Cowan, 2020).…”
Section: Evidence On Employment Impacts and The Role Of Policiesmentioning
confidence: 99%